INSULIN RESISTANCE MARKERS IN PATIENTS WITH ST SEGMENT ELEVATION MYOCARDIAL INFARCTION - O. V. Gruzdeva; O. L. Barbarash; O. E. Akbasheva; E. I. Palicheva; V. V. Kashtalap; Yu. A. Dyleva; A. A. Silonova; E. V. Tavlueva (Российский кардиологический журнал, 2011)
In general population and among diabetic patients, insulin resistance (IR) is regarded as a cardiovascular risk factor. The aim of this study was to assess the dynamics of IR markers among non-diabetic and diabetic (Type 2 diabetes mellitus, DM-2) patients with acute myocardial infarction and ST segment elevation (STEMI) in the acute and early reconvalescent phases. In non-diabetic patients, clinical course of STEMI was characterised by IR development, postprandial hyperglycemia and hyperinsulinemia, as well as elevated levels of free fatty acids (FFA) and plasminogen activator inhibitor (PAI). Persistent high levels of FFA and PAI during stabilization phase in STEMI patients could justify the use of IR markers as one of the criteria for DM-2 risk and for the start of secondary prevention of metabolic MI complications.